Rice husk-derived sodium silicate as a highly efficient and low-cost basic heterogeneous catalyst for biodiesel production. (1st July 2016) - Roschat, Wuttichai; Siritanon, Theeranun; Yoosuk, Boonyawan; Promarak, Vinich
Graphical abstract: Rice husk-derived sodium silicate exhibits high potential as a low-cost solid catalyst for industrial biodiesel production. Highlights: Rice husk-derived sodium silicate was employed as a high performance catalyst for biodiesel production. 97% yield of FAME was achieved in 30 min at 65 °C. The room-temperature transesterification gave 94% yield of FAME after only 150 min. Abstract: In the present work, rice husk-derived sodium silicate was prepared and employed as a solid catalyst for simple conversion of oils to biodiesel via the transesterification reaction. The catalyst was characterized by TG–DTA, XRD, XRF, FT-IR, SEM, BET and Hammett indicator method. Under the optimal reaction conditions of catalyst loading amount of 2.5 wt.%, methanol/oil molar ratio of 12:1, the prepared catalysts gave 97% FAME yield in 30 min at 65 °C, and 94% FAME yield in 150 min at room temperature. The transesterification was proved to be pseudo-first order reaction with the activation energy ( Ea ) and the frequency factor ( A ) of 48.30 kJ/mol and 2.775 × 10 6  min −1 respectively. Purification with a cation-exchange resin efficiently removed all soluble ions providing high-quality biodiesel product that meets all the ASTM and EN standard specifications. Rice husk-derived sodium silicate showed high potential to be used as a low-cost, easy to prepare and high performance solid catalyst for biodiesel synthesis.